Relationship among psychotic features, benzodiazepine receptor agonists, and rehospitalization in patients with electroconvulsive therapy‐responsive major depressive disorder: A retrospective 2‐year observational study - Akise Umakoshi; Masahiro Takeshima; Yu Itoh; Mari Yamamoto; Nana Shibata; Masaya Ogasawara; Naoko Ayabe; Kazuo Mishima (Wiley, 2022)
Abstract Aim It is controversial whether psychotic features are a risk factor for relapse in patients with electroconvulsive therapy‐responsive major depressive disorder. A recent study reported that benzodiazepine receptor agonists reduce relapse of psychotic depression. As long‐term use of these agonists may induce dependence, further research is required. We examined whether psychotic features are associated with rehospitalization in electroconvulsive therapy‐responsive major depressive disorder patients. We also investigated whether taking benzodiazepine receptor agonists at the end of electro‐convulsive therapy was associated with rehospitalization among patients with psychotic depression. Methods This study included 47 hospitalized patients (22 with psychotic depression, 25 with non‐psychotic depression) who had responded to electroconvulsive therapy. Rehospitalization for major depressive episodes within two years from the last session was investigated. Results Twenty‐three subjects (49%) were rehospitalized during the two‐year follow‐up. Kaplan-Meier analysis revealed no difference in rehospitalization between patients with psychotic and non‐psychotic depression (Log‐rank P = 0.87). Among the 22 responders to electroconvulsive therapy with psychotic depression, there was no difference in benzodiazepine receptor agonist use at the end of electroconvulsive therapy between the rehospitalization and non‐rehospitalization groups. Conclusion Our exploratory study found no difference in the benzodiazepine receptor agonists use at the end of electroconvulsive therapy between rehospitalization and non‐rehospitalization groups in patients with electroconvulsive therapy‐responsive psychotic depression. Thus, the relapse‐preventing effect of these agonists in psychotic depression should be investigated in future randomized controlled trials. Further research is also needed to determine whether psychotic features are associated with rehospitalization in these patients.